Atrial Undersensing-Associated Premature Atrial Contractions: A Case Report - Skakun, Oleksiy; Vandzhura, Yaroslava; Vandzhura, Ihor; Symchych, Khrystyna; Symchych, Anton (Scripta Medica, 2024)
Atrial undersensing is defined as the inability of the pacemaker to detect spontaneous atrial activity. A case of premature atrial contractions associated with atrial undersensing is presented. A 33-year-old woman presented with irregular heartbeat and general weakness. A single atrial stimulation (AAI) pacemaker was implanted seven years earlier for recurrent syncope associated with sinus arrest. Ambulatory ECG monitoring revealed multiple episodes of atrial undersensing resulting in premature atrial contractions (PACs). Occasionally, blocked PACs or PACs with aberrancy associated with atrial undersensing were seen. After improvement of atrial sensing, no episodes of undersensing were found and the complaints disappeared.